Cytokinin-Induced Wall Extensibility in Excised Cotyledons of Radish and Cucumber - Thomas, Jerry (1981)
The mechanism of cytokinin-induced cell expansion in cotyledons excised from dark-grown seedlings of radish (Raphanus sativus L.) and cucumber (Cucumus sativus L.) was studied. Cotyledons were incubated in dim light with or without 17 micromolar zeatin for periods up to 3 days. Fresh weights and osmotic potentials were measured daily. Cell wall extensibility properties were measured before and after the growth period. Also, experiments in which radish cotyledons were grown in mannitol solutions of various concentrations were performed. Comparisons of growth rates and increases of tissue osmotic potentials (toward zero) during growth without mannitol indicate that wall extensibility increased during the growth period and that this extensibility was enhanced by zeatin. Extensibility values derived from growth rates in mannitol provided indirect evidence of zeatin-increased wall extensibility. These conclusions were verified by direct measurements of plasticity with an Instron extensiometer. Thus, growth stimulation of excised cotyledons by cytokinins apparently involves wall loosening, in addition to previously demonstrated increases of K(+) absorption and formation of reducing sugars.